Why do patients come to the emergency department after using cannabis?. (2nd June 2020) - Shelton, Shelby K.; Mills, Eleanor; Saben, Jessica L.; Devivo, Michael; Williamson, Kayla; Abbott, Diana; Hall, Katelyn E.; Monte, Andrew A.
Abstract: Background: Cannabis (MJ) policy liberalization in a majority of US states has impacted emergency department (ED) visits. It is important to understand why people come to the ED after using MJ because the drug is now available to experienced and naïve people across the country. The objectives of this study were to (1) improve upon administrative dataset methodology by performing additional chart review to describe ED visits related to cannabis, (2) understand why patients come to the ED after using cannabis, and (3) begin to inform our understanding of cannabis-attributable ED visits to start to educate patients and providers about cannabis' safety. Methods: We performed a retrospective chart review of ED visits identified by cannabis ICD-9 and 10-CM codes between 2012 and 2016. Visits were reviewed and determined if the visit was partially attributable to cannabis based upon a pre-specified definition, then categorized into clinical complaint categories. Descriptive statistics, Chi-Square, and T-tests were used to elucidate the data. Results: About one-fourth (25.74%) of visits with cannabis ICD-CM codes were found to be at least partially attributable to cannabis. These patients are more often young, Caucasian males when compared to the overall ED population ( p < .0001). Patients with a cannabis-attributable visit were more often admitted to the hospital ( p < .0001). The most common complaints in cannabis-attributable visits were gastrointestinal and psychiatric complaints, as well as intoxication. The number of cannabis-attributable visits rose with time ( p =.012). Conclusions: Based on a pre-specified definition, with good inter-rater reliability, we found that 25% of visits with a cannabis ICD-CM code were partially attributable to cannabis. These findings represent areas to target in cannabis user education as public perceptions change across time.